The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/metabo13080950
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Salivary Amino Acid Levels in Cancer

Abstract: This review analyzed 21 scientific papers on the determination of amino acids in various types of cancer in saliva. Most of the studies are on oral cancer (8/21), breast cancer (4/21), gastric cancer (3/21), lung cancer (2/21), glioblastoma (2/21) and one study on colorectal, pancreatic, thyroid and liver cancer. The amino acids alanine, valine, phenylalanine, leucine and isoleucine play a leading role in the diagnosis of cancer via the saliva. In an independent version, amino acids are rarely used; the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…34 Polyamine profiles in plasma and urine showed discriminative patterns between lung and liver cancer. 28 Additionally, elevated N 1 ,N 12 -diacetylspermine levels in the urine have been frequently reported in various cancers. 35,36 A high plasma concentration of N 1 ,N 12 -diacetylspermine has also been observed in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Polyamine profiles in plasma and urine showed discriminative patterns between lung and liver cancer. 28 Additionally, elevated N 1 ,N 12 -diacetylspermine levels in the urine have been frequently reported in various cancers. 35,36 A high plasma concentration of N 1 ,N 12 -diacetylspermine has also been observed in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…28 Additionally, elevated N 1 ,N 12 -diacetylspermine levels in the urine have been frequently reported in various cancers. 35,36 A high plasma concentration of N 1 ,N 12 -diacetylspermine has also been observed in patients with lung cancer. 37 We previously reported that N 1 -acetylspermidine had the highest discrimination ability among all metabolites in saliva samples collected from patients with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important part of the metabolomic profile, which makes it possible to discriminate between BC patients and healthy controls, is represented by amino acids. Amino acids in breast cancer are determined in the tissue [ 25 , 26 , 27 ], serum [ 7 , 28 , 29 , 30 ], plasma [ 6 , 31 , 32 , 33 , 34 ], saliva [ 35 , 36 , 37 , 38 ], and urine [ 39 , 40 , 41 ]. Amino acids not only play a vital role in the synthesis of biological molecules such as proteins in malignant cancer cells, but they are also important metabolites for immune cell activation and antitumor activity in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%